2003
DOI: 10.1136/bmj.326.7392.733
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of conventional cervical smear, monolayer cytology, and human papillomavirus DNA testing for cervical cancer screening

Abstract: Objectives To compare the sensitivity, specificity, and interobserver reliability of conventional cervical smear tests, monolayer cytology, and human papillomavirus testing for screening for cervical cancer. Design Cross sectional study in which the three techniques were performed simultaneously with a reference standard (colposcopy and histology). Setting Public university and private practices in France, with complete independence from the suppliers. Participants 828 women referred for colposcopy because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
2
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 26 publications
6
71
2
7
Order By: Relevance
“…3 Among the studies with an adequate reference standard such as colposcopy/biopsy, women are often selectively followed based on any previous detection of cytological abnormality or the presence of other risk factors for cervical disease. Besides the current study, only 2 studies to date (a Costa Rican study of 8,636 women from a population-based sample 26 and a French study of 1,757 women attending public and private clinics for routine cytologic screening 27 ) have avoided selective follow-up of high-risk or cytologically positive women and applied a definitive clinical reference standard to either a random sample of women with normal screening test results or the entire sample of women. This is critical to allowing the comparative sensitivity and specificity for LBC and conventional cytology to be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…3 Among the studies with an adequate reference standard such as colposcopy/biopsy, women are often selectively followed based on any previous detection of cytological abnormality or the presence of other risk factors for cervical disease. Besides the current study, only 2 studies to date (a Costa Rican study of 8,636 women from a population-based sample 26 and a French study of 1,757 women attending public and private clinics for routine cytologic screening 27 ) have avoided selective follow-up of high-risk or cytologically positive women and applied a definitive clinical reference standard to either a random sample of women with normal screening test results or the entire sample of women. This is critical to allowing the comparative sensitivity and specificity for LBC and conventional cytology to be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Two studies of cervical cytology showed that agreement was similar whether liquid-based or conventional cytology preparations were used. 26,27 Few studies have evaluated the reliability of anal specimen reporting. [17][18][19] Scholefield et al 17 circulated 30 cytology slides with material obtained from the perianal skin to 6 pathologists and reported point estimates of pairwise agreement ranging from 0.65 (moderate) to 1.00 (perfect).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have challenged this notion, and to date, the question remains largely unanswered (20,70,71). A systematic review of 56 published studies that included over 1 million slides recently addressed the current literature on this subject (19).…”
Section: Conventional Pap Screening Versus Liquid-based Cytologymentioning
confidence: 99%